Exploring the HeLa Dark Mitochondrial Proteome - Marini, Federica; Carregari, Victor Corasolla; Greco, Viviana; Ronci, Maurizio; Iavarone, Federica; Persichilli, Silvia; Castagnola, Massimo; Urbani, Andrea; Pieroni, Luisa (Frontiers in Cell and Developmental Biology, 2020)
In the framework of the Human Proteome Project initiative, we aim to improve mapping and characterization of mitochondrial proteome. In this work we implemented an experimental workflow, combining classical biochemical enrichments and mass spectrometry, to pursue a much deeper definition of mitochondrial proteome and possibly mine mitochondrial uncharacterized dark proteins. We fractionated in two compartments mitochondria enriched from HeLa cells in order to annotate 4230 proteins in both fraction by means of a multiple-enzyme digestion (trypsin, chymotrypsin and Glu-C) followed by mass spectrometry analysis using a combination of Data Dependent Acquisition and Data Independent Acquisition. We detected 22 mitochondrial dark proteins not annotated for their function and we provide their relative abundance inside the mitochondrial organelle. Considering this work as a pilot study we expect that the same approach, in different biological system, could represent an advancement in the characterization of the human mitochondrial proteome providing uncharted ground to explore the mitonuclear phenotypic relationships. All spectra have been deposited to ProteomeXchange with PXD014201 and PXD014200 identifier.